The n-alkylresorcinols in durum wheat: genotypic and environmental variability - Ciccoritti R.; Bellato S.; Frate V.; Nocente F. (Proceedings of the International Symposium on Genetics and breeding of durum wheat, 2014)
The polyphenols commonly present in some cereal grains (Triticum species, rye and barley, mainly) include the 5-n-alkylresorcinols, alternatively called alkylresorcinols (ARs). The major AR in cereal grain contains the saturated chain with an odd number of carbon atoms in the range 17-25. These polyketides exhibit a wide spectrum of biological activities (antimicrobial, interaction with proteins, biological membranes, and enzymatic activities) which may be associated with their amphiphilic structure. Content and composition of ARs are affected by several factors such as plant species, cultivar, organ, physiological stage and environment. The aim of the present study was to evaluate AR variability (content and homologue composition) by GC-MS of fifteen cultivars of durum wheat grown in three Italian locations (Jesi, Montelibretti and Foggia) during 2009 and 2010. The environment (E) and the genotype (G), as well as their interaction (GxE), appeared to significantly influence the AR content in the durum wheat grains. On average, the analysed genotypes showed a variability range from 173.9 to 415.2 μg/g (dry matter, DM) and revealed similar composition of AR homologues with a high proportion of higher chain length C21:0, C23:0 and C25:0. Finally, in the present study the potential antifungal activity of ARs extracted from durum wheat against four different Fusarium species was also described.
International Symposium : Genetics and Breeding of Durum Wheat, 2013/05/27-30, Rome (Italy)